Unveiling the SEI layer formed on pillar-structured MXene anode towards enhanced Li-ion storage. (September 2021) - Zhao, Nana; Yang, Yijun; Xiao, Yubao; Wang, Chong; Ha, Minh Ngoc; Cui, Weibin; Wang, Xi
Abstract: The importance of the solid electrolyte interphase (SEI) layer for enhanced Li-ion storage has been well established, but primary understanding of the chemical components and structure of SEI layer on MXene-based electrodes remains incomplete. Here, we characterized the morphology and components of SEI layer on Ti3 C2 Tx and Ti3 C2 Tx /Fe2 O3 electrode materials through combination of X-ray photoelectron spectroscopy (XPS), Fourier transform infrared spectroscopy (FT-IR), Raman spectroscopy and transmission electron microscopy (TEM). The results show the SEI layer formed on pillar-structured Ti3 C2 Tx /Fe2 O3 is dense and intact after long cycling, while the SEI layer on Ti3 C2 Tx electrode is noncontinuous. The pillar-structured Ti3 C2 Tx /Fe2 O3 exhibits significantly enhanced capacity of 449.6 mAh g −1 at 300 mA g −1 after 100 cycles compared with Ti3 C2 Tx (140.2 mAh g −1 ) owing to the intact SEI layer with friendly chemical components. This work elaborates a recognition for SEI layer in MXene-based electrode, which provides a useful strategy for further SEI engineering. Graphical abstract: Image, graphical abstract